The Conceptual Knowledge Test to Measure The Physics Concepts Mastery of Biology Students on Waves Topic - Wulandari, Dewi; Rangkuti, Muhammad Aswin; Tanjung, Yul Ifda; Ramadhani, Irham; Elvianasti, Mega (Department of Physics, Faculty of Mathematics and Natural Sciences, 2024)
Waves is one of the Physics materials that must be mastered and understood. Students need help describing the mechanism of wave movement, so it is necessary to develop a test instrument tailored to the scientific field of Biology. Therefore, the study aimed to develop a Wave conceptual knowledge test instrument that can be used to train and measure the mastery of Physics concepts of the Wave topic of Biology Department students that meet the instrument's feasibility, including content validity, reliability, and difficulty level. This research uses the 4D development model (Four-D models), which consists of four stages: Define, Design, Development, and Disseminate. Instruments-based feasibility is based on content validity, test reliability, and difficulty level. Based on the study results, the instruments developed were based on indicators of achievement of Physics competencies for Biology Department students. The content was adjusted to the field of Biology, namely the concept of waves in the human and animal hearing system. The test instrument met the criteria, namely content validity, test reliability, and difficulty level, so this instrument can be used to train and measure the physics concept mastery of Biology students. The wave topic adapted to the scientific field of Biology can help Biology students understand the wave concepts correctly.